PD-1 and PDL-1 Immune Checkpoint Inhibitors: Emerging Hope for the Future of Lung Cancer Immunotherapy - Ilyasa, Muhammad Riza; Ramadhani, Muhammad Zulmi; Santoso, Rex Jeremy; Hutasoit, Gina Andyka; Miskad, Upik Anderiani (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2025)
Background: Lung cancer is the leading cause of cancer-related deaths worldwide, with Non-Small Cell Lung Cancer (NSCLC) being the most common type. Despite advances in treatment, the prognosis remains poor. Immune checkpoint inhibitors targeting PD-1 and PD-L1 have emerged as a promising first-line treatment approach in combating cancer. Objectives: This literature review aims to evaluate the effectiveness of PD-1 and PD-L1 immune checkpoint inhibitors in the treatment of NSCLC. It also explores the potential of these inhibitors to improve patient survival rates compared to conventional therapies. Methods: A systematic literature search was conducted using databases such as PubMed, Google Scholar, ScienceDirect, and NCBI, with keywords including "PD-1," "PD-L1," "NSCLC," "lung cancer," and "immunotherapy." Results: All four inhibitors significantly improve survival rates compared to traditional chemotherapy. Atezolizumab and pembrolizumab show high effectiveness in patients with high PD-L1 expression. Durvalumab, when combined with chemotherapy, overcomes resistance mechanisms. Nivolumab, enhancing survival rates. Conclusion: PD-1 and PD-L1 inhibitors provide substantial benefits in the treatment of NSCLC, including increased survival rates and reduced need for aggressive therapies. Further research should focus on optimizing combination therapies to expand the therapeutic benefits of these inhibitors.